Sustainable and cost-effective synthesis of NiO/ZnO hybrid materials utilizing guava extract for the efficient photodegradation of methylene blue under natural sunlight irradiation - Zeenat bibi; Aneela Tahira; Muhammad Ali Bhatti; Mazhar Ali Abbasi; Imran Ali Halepoto; Matteo Tonezzer; Elmuez Dawi; Rafat M. Ibrahim; Ahmed Ali Hulio; Quratulain Balouch; Zafar Hussain Ibupoto (Results in Engineering)
In wastewater treatment applications, the development of cost-effective, earth-abundant, efficient, and environmentally friendly photocatalysts presents significant challenges. This study focuses on the fabrication of NiO/ZnO composites using varying concentrations of rotten guava fruit juice. Scanning electron microscopy (SEM) analysis revealed that the composites exhibit nanoparticle-like morphologies. The crystalline structure of the composites was analyzed using powder X-ray diffraction, which identified NiO in a face-centered cubic phase and ZnO in a hexagonal phase. Optical properties were examined via ultraviolet-visible spectroscopy, while Fourier transform infrared spectroscopy was employed to identify surface functional groups. Among the samples, the NiO/ZnO composite synthesized with 6 mL of rotten guava fruit juice (sample 3) demonstrated exceptional photocatalytic activity under natural sunlight irradiation, achieving a degradation efficiency of 97.9 % for 2.1 × 10−5 M of methylene blue in aqueous solution and catalyst dose of 15 mg. The dye degradation efficiency was found highest at the pH 12 of dye solution and a 15 mg of catalyst dose. At higher concentration of dye of 4.37×10−5 M, the sample 3 has shown degradation efficiency of 79 %. A scavenger study identified hydroxyl radicals as the primary reactive species involved in methylene blue degradation. Furthermore, sample 3 retained its structural integrity after five recycling tests.